MEMBANGUN SEMANGAT KEBANGSAAN PERSPEKTIF ETIKA HINDU - I Made Hartaka (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Hindu ethics are good and bad rules of human actions that are based on Hindu teachings. Hindu ethics reveal how to get along, sit, walk, eat and drink, sleep and dress. There are standards that must be followed, as in the pattern of associating with all people regardless of ethnicity, race and religion. Humans are essentially living creatures that describe the value of God into the natural environment and the activities they do. The activities of human or associating use the value of God as a basis for moving forward in order to become better. efforts that can be made by Hindus include keeping the mind with a noble common goal, speaking in order to support that goal, and making a serious effort to realize it. all efforts undertaken for the nobler public interest become a tangible manifestation of the brotherhood among the children of the nation. this common goal can only be realized if we are able to control the emotion and personal interests. Everything must be able to set forth in various opportunities to achieve life goals “Moksartam Jagathita ya ca iti Dharma”